KEMAMPUAN KOMPETISI RELATIVE TEBU-PRG EVENT-5 TERHADAP GULMA DAUN SEMPIT DAN DAUN LEBAR MELALUI PENDEKATAN REPLACEMENT SERIES (RELATIVE COMPETITIVE ABILITY OF SUGARCANE EVENT-5 AND ITS PRIMARY WEEDS USING REPLACEMENT SERIES APPROACH) - Netty Ermawati; Nurmala Sari; Novita Cholifah Ida; Bambang Sugiharto (Jurnal Ilmiah Inovasi, 2016)
Event-5 is a genetically modified (GM) sugarcane that engineered by introducing the Sucrose-Phosphate Synthase (SPS) gene to enhance the sugar productivity. To fulfill the security requirements of genetically modified products in the safety agriculture and the enviroment, it is necessary to test the competitive ability to the primary weeds which grow in the sugarcane cultivation areas. This study aimed to determine whether the transgenic sugarcane (Event-5) potentially invasive to the weeds at the critical stage of growth, that could effect the environmental balances. This research was conducted at Screen House and Laboratory for Biosciences, State Polytechnic of Jember, designed using the replacement series method in a Randomized Complete Block Design without factorial treatment. The combination treatments were Event-5, Non-transgenic sugarcane (NT) and the weeds (Ciperus rotundus and Portulaca olecarea) densities which consists of thirty-three treatments. The competitive ability test was determined by the rate of vegetative growth and the relative dry weight biomass of Event-5, NT plant and the weeds. The results indicated that the growth rate of Event-5, as well as the accumulation of dry weight of transgenic sugarcane were highly decrease than those of the weeds. The relative crowding coefficient (RCC) value of Event-5 showed lower compared to the P. olecarea weed, and sligtly higher to the C. rotundus weed. The RCC value of weed (C. rotundus) was higher than the RCC value of Event-5, suggested that the weed was potentially invasive to the transgenic sugarcane, and the Event-5 was not potential as a weed.Â